Transcriptome Analysis of Phycocyanin-Mediated Inhibitory Functions on Non-Small Cell Lung Cancer A549 Cell Growth - Shuai Hao; Shuang Li; Jing Wang; Lei Zhao; Yan Yan; Qi Cao; Tingting Wu; Liyun Liu; Chengtao Wang (Marine Drugs, 2018)
Phycocyanin (PC), derived from cyanobacteria and Spirulina cells, is a type of natural antineoplastic marine protein. It has been reported that phycocyanin exerts an antitumor function in non-small cell lung cancer (NSCLC) cells, but the underlying mechanism has not been elucidated. In this research, a transcriptome study was performed to investigate the regulatory mechanisms of phycocyanin on human NSCLC A549 cells. The survival rate and proliferation ability of A549 cells were markedly reduced by phycocyanin, along with abnormal morphologic changes. The transcriptome analysis showed that 2970 genes were differentially expressed after phycocyanin treatment in A549 cells, including 1431 down-regulated and 1539 up-regulated genes. Gene ontology and KEGG analysis suggested that some classical pathways, such as Wnt, NF-κB, and PI3K-AKT signaling, were significantly enriched. Strikingly, protein⁻protein interaction (PPI) analysis showed that ubiquitin-C (UBC) occupied the highest degree (the highest number of interactions) in differential genes, indicating that it might play a key role in the phycocyanin-mediated regulatory process in A549 cells. Moreover, qRT-PCR results showed consistent expression trends of differential genes with transcriptome analysis. Consequently, this study has provided a theoretical basis for regulation of phycocyanin in A549 cells, which lays a foundation for the treatment of NSCLC.